The Influence of Product Attributes and Consumer Prefer-ences on Single Origin Coffee Purchasing Decisions at Sala-pan Djati Coffee - Vetto Agung Prabowo; Puji Isyanto; Neni Sumarni (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of product attributes and consumer preferences on the purchasing decision of single origin coffee at Salapan Djati Coffee. Single origin coffee, as one of Indonesia’s leading commodities, holds great potential in the coffee industry, both for the domestic and export markets. The method used in this research is a quantitative verification design with a purposive sampling technique, involving consumers who have purchased and consumed V60 single origin coffee. Data analysis was conducted using SmartPLS version 4.0. The research results show that product attributes—such as quality, price, and brand—have a significant influence on purchasing decisions by 14.79%, and consumer preferences also show a positive influence on purchasing decisions by 18.08%. Simultaneously, these factors have a significant combined influence of 32.48%. These findings provide strategic insights for producers and marketers to align products with consumer needs, enhance preferences, and strengthen marketing strategies to compete in the coffee market..